Pojawienie się filozofii w Europie i faktu tego następstwa - Pałubicka, Anna (Filozofia Publiczna i Edukacja Demokratyczna, 2012)
In this paper the author attempts to answer the question why the European culture – since the sixteenth century – has gained a civilizational advantage over other cultural circles. The proposed answer focuses on philosophy and its genesis. The author concludes that the emergence of philosophy constitutes new, hitherto unknown way of thinking which has overcome the „magical thought”. Spectacular transformations of European culture, therefore, seem to begin with philosophical thinking, i.e. with the emergence of philosophy.